Directory of chemical producers and products chemical enterprises in the mediterranean region - United Nations. Economic Commission for Europe (New York United Nations, 1993)
Annual.
Keywords: Chemical industry -- Europe -- Directories; Chemical industry -- Directories; Chemicals -- Directories; Chemicals -- Europe -- Directories